TERESA MARAT-MENDES, SARA SILVA LOPES, JOÃO CUNHA BORGES, PATRÍCIA BENTO D'ALMEIDA - Atlas of the Food System. Challenges for a Sustainable transition of the Lisbon Region - Sucena, Sara (ZARCH, 2024)
TERESA MARAT-MENDES, SARA SILVA LOPES, JOÃO CUNHA BORGES, PATRÍCIA BENTO D'ALMEIDAAtlas of the Food System. Challenges for a Sustainable transition of the Lisbon RegionSpringer, Cham (Suiza), 2022, LVII, 314 pp. Tapa dura. 246,09 €Idioma: inglésISBN-10: ‎ 3030948323ISBN-13: ‎ 978-3030948320